Cinacalcet Treatment of Primary Hyperparathyroidism - H. M. Rothe; O. Liangos; P. Biggar; A. Petermann; M. Ketteler (International Journal of Endocrinology)
Although parathyroidectomy remains the only curative approach to most primary hyperparathyroidism cases, medical treatment with cinacalcet HCl has been proven to be a reasonable alternative for several patient subgroups. Cinacalcet almost always controls hypercalcemia and hypophosphatemia sufficiently. PTH levels are lowered, and cognitive parameters improve. While an increase in bone mineral density DEXA scan scores was not demonstrated in cinacalcet trials, the same applies to more than half of patients after parathyroidectomy. Medical therapy should be first choice in patients with hyperplasia in all glands rather than an isolated adenoma (10–15%), patients with persisting HPT following unsuccessful surgery or inoperable cases due to comorbidities, and patients detected in lab screens for hypercalcemia before developing symptoms who should be treated early but are usually reluctant to undergo surgery. Nephrolithiasis was not found to occur more frequently in cinacalcet trial groups, but urine calcium excretion as one major risk factor of this complication of primary HPT may increase on cinacalcet. Patients carrying the rs1042636 polymorphism of the calcium-sensing receptor gene respond more sensitively to cinacalcet and have a higher risk of calcium stone formation. Cinacalcet is usually administered twice daily but three or four doses per day should be discussed to mimic the beneficial pulsatile PTH-pattern.